Efektivitas Penggunaan Google Classroom Dalam Pembelajaran Daring Terhadap Hasil Belajar Siswa Pada Materi Bangun Ruang Di Kelas VI SDN Cibonteng Kecamatan Walantaka Kota Serang - Marlena, Lena; Tiurlina, Tiurlina; Alfarisa, Fitri (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Online learning is learning that uses online applications to support learning activities. One of the online applications that can be used as online learning media is Google Classroom. Based on the results of interviews with the sixth-grade teacher of the State Elementary School of Cibonteng, it can be seen that mathematics is the subject that is considered the most difficult by students, especially geometry. This study aims to determine the effectiveness of online learning using Google Classroom on building materials at State Elementary School of Cibonteng, Walantaka District, Serang City on student learning outcomes. The research method used is a pre-experimental design, and the research design is a set of pretest-posttest designs. Data collection techniques in this study were interviews, observation, and written tests. The data analysis technique used in this research is the normality test of the data and the hypothesis test. The results showed that the use of Google Classroom in online learning could effectively improve student learning outcomes in the geometry material, this can be seen from the results of the paired t-test with the pretest and post-test results are 0.16, meaning that the p-value 0.05, then H0 accepted and Ha rejected. In addition, the results of the Google Classroom N-Gain Test are 0.12, which means they are in the low category. These results show that this learning influences students' learning success. These practices can be the basis for selecting and improving teachers in the future.